Contention-Based Polling Efficiency in Broadband Wireless Networks - Andreev, Sergey D.; Turlikov, Andrey M.; Vinel, Alexey V. (Analytical and Stochastic Modeling Techniques and Applications, 2008)
This paper addresses the performance of the contention-based polling techniques at the bandwidth reservation stage of IEEE 802.16 standard. A general proposition is proved, which establishes that the grouping of users in the random multiple access system does not change its capacity. Broadcast and multicast polling mechanisms are then considered, for which the throughput and the rate of the truncated binary exponential backoff algorithm are calculated for the lossy and the lossless system types, respectively. It is shown, that subject to proper optimization the performance of the aforementioned algorithm is the same for both system types. The efficiency of the symmetric user grouping is finally studied, which demonstrates that a negligible performance gain may be achieved for the cost of the increased IEEE 802.16 overhead.